400 MHz GPR profile Troll Station - South Pole (IPY 2007-2009) - Kohler, Jack; Tronstad, Stein (Norwegian Polar Institute, 2010)
Radar profiles of the upper 50-90 m of the snowpack along the route of the Norwegian-U.S. IPY traverse of East Antarctica. The radar was run primarily as a crevasse detector, but the data has been kept for comparison with other radar data from the traverse. The scientific objectives are to investigate the spatial and temporal variability in snow accumulation over this area of Antarctica, and to validate remote sensing data. ### Route - Leg 1 (2007-2008): - **From:** Troll station [-72.01, 2.53] - **To:** "Camp Winter" [-86.8, 54.4] - Leg 2 (2008-2009): - **From:** South pole [-90, 0] - **Across:** Recovery lakes region - **To:** Troll station [-72.01, 2.53] ### Instruments - GSSI TerraSIRch 3000 ground penetrating radar, with 400 MHz antenna